2021
DOI: 10.1111/scd.12636
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene in patients with motor neuron disease requires attention: A cross‐sectional survey study

Abstract: Aims: Motor Neuron Disease (MND) is a progressive neurodegenerative neuromuscular disease, which can progressively impair arm-hand function. Needs and barriers of MND patients and their caregivers in performing oral hygiene were studied. Methods: An online survey was sent to 706 MND patients. The questions of the survey included self-reliance, self-reported oral health, and oral hygiene.The oral health-related quality of life (GOHAI-NL) and the subjective well-being (ALSAQ-5) were also measured.Results: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Snowball sampling participants with the help of participants on recruiting other participants for the study Internet-based online survey Self-reported OHRQoL (OHIP-14), free text questions addressing participants' satisfaction with the dental treatment and the health care system Nam et al-2017-Korea [ 50 ] Healthy university students in Korea (age > = 20) 130 (NA) A random sampling of students in 3 majors at Kangwon University Dogye Campus An Internet-based online survey using Google Forms (Google LLC., Mountain View, CA, USA) Self-reported quality of life, dental health status, and education Mortimer-Jones et al-2018-Australia [ 51 ] Australian healthy nursing students across all year levels 281 (25%) Snowball sampling that study info was circulated by staff members and publicized during lectures. Convenience sampling by recruiting all nursing students in email form An Internet-based online survey using SurveyMonkey (Momentive Inc., San Mateo, CA, USA) Self-reported anxiety and temporomandibular-related symptoms, and quality of life (OHIP-TMD and PROMIS® short form) Liu-2021-China [ 52 ] Chinese Healthy Kids (3–6) 4495 (NA) Convenience sampling with online recruitment using a recruitment link or quick response (QR) code to be distributed to groups in their WeChat Internet-based survey platform Proxy-reported oral health status, care behavior, and caregivers’ attitudes Snowball sampling that people can recruit other participants by sharing the link Makizodila-2021-Netherlands [ 53 ] Motor Neuron Disease (MND) patients in Netherland 259 (36.7%) Convenience sampling on caregivers of all registered MND patients in the Netherlands in the Prospective ALS study Netherlands Database by an email newsletter of the Dutch ALS Centre Email Self- and proxy-reported OHRQoL (GOHAI) and their performance on oral hygiene Kotzer et al-2012-Canada [ 54 ] Canadian healthy pre-seniors and seniors …”
Section: Resultsmentioning
confidence: 99%
“…Snowball sampling participants with the help of participants on recruiting other participants for the study Internet-based online survey Self-reported OHRQoL (OHIP-14), free text questions addressing participants' satisfaction with the dental treatment and the health care system Nam et al-2017-Korea [ 50 ] Healthy university students in Korea (age > = 20) 130 (NA) A random sampling of students in 3 majors at Kangwon University Dogye Campus An Internet-based online survey using Google Forms (Google LLC., Mountain View, CA, USA) Self-reported quality of life, dental health status, and education Mortimer-Jones et al-2018-Australia [ 51 ] Australian healthy nursing students across all year levels 281 (25%) Snowball sampling that study info was circulated by staff members and publicized during lectures. Convenience sampling by recruiting all nursing students in email form An Internet-based online survey using SurveyMonkey (Momentive Inc., San Mateo, CA, USA) Self-reported anxiety and temporomandibular-related symptoms, and quality of life (OHIP-TMD and PROMIS® short form) Liu-2021-China [ 52 ] Chinese Healthy Kids (3–6) 4495 (NA) Convenience sampling with online recruitment using a recruitment link or quick response (QR) code to be distributed to groups in their WeChat Internet-based survey platform Proxy-reported oral health status, care behavior, and caregivers’ attitudes Snowball sampling that people can recruit other participants by sharing the link Makizodila-2021-Netherlands [ 53 ] Motor Neuron Disease (MND) patients in Netherland 259 (36.7%) Convenience sampling on caregivers of all registered MND patients in the Netherlands in the Prospective ALS study Netherlands Database by an email newsletter of the Dutch ALS Centre Email Self- and proxy-reported OHRQoL (GOHAI) and their performance on oral hygiene Kotzer et al-2012-Canada [ 54 ] Canadian healthy pre-seniors and seniors …”
Section: Resultsmentioning
confidence: 99%
“…and ALS, 82 reducing access to the oral cavity for routine care or exams. Despite these many potential barriers to oral care, this problem is often overlooked during routine clinic visits 83 …”
Section: Neuromuscular Respiratory Care: General Principlesmentioning
confidence: 99%
“…Despite these many potential barriers to oral care, this problem is often overlooked during routine clinic visits. 83 Oral hygiene interventions to reduce risk of pneumonia have been studied in persons with neurological diagnoses and other highrisk populations. A population-based retrospective study involving 3632 children with neurological impairment and history of prior hospitalizations for pneumonia found dental care to be the only intervention associated with reduced recurrence of severe pneumonia.…”
Section: Oral Hygienementioning
confidence: 99%
“…Additionally, a mouth gag can aid in cleaning and during dental treatment to facilitate mouth opening and provide access during dental work [ 13 , 14 ]. A study in the Netherlands found that most patients with ALS were not satisfied with their daily oral care [ 15 ]. Thus, the caregiver and the clinician must discuss the best possible strategies for dental care.…”
Section: Reviewmentioning
confidence: 99%